Relative efficacy of treatment options in transplant-ineligible newly diagnosed multiple myeloma: results from a systematic literature review and network meta-analysis. Issue 3 (23rd February 2020) - Ramasamy, Karthik; Dhanasiri, Sujith; Thom, Howard; Buchanan, Vanessa; Robinson, Suzanne; D'Souza, Vijay K.; Weisel, Katja
Abstract: Established treatments for transplant-ineligible (TNE) patients with newly diagnosed multiple myeloma (NDMM) include melphalan and prednisone (MP) combined with either bortezomib (VMP) or thalidomide (MPT), or lenalidomide plus low-dose dexamethasone (Rd). New treatments for TNE NDMM include Rd plus bortezomib (RVd) and daratumumab plus VMP (VMP + D), daratumumab plus lenalidomide and dexamethasone (D + Rd). Relative efficacy of these treatments was compared using a network meta-analysis. Eight trials identified by a systematic literature review were included in the primary analysis; hazard ratios (HRs) for overall survival (OS) and progression-free survival (PFS) were used. Rd was superior to other MP-based regimens for OS and PFS. There was strong evidence that, compared with Rd, both D + Rd and RVd improved PFS (HR 0.57; 95% credible interval (CrI) 0.43, 0.73 and HR 0.72; 95% CrI 0.56, 0.91, respectively). However, there was strong evidence only for RVd in respect to OS (HR 0.72; 95% CrI 0.52, 0.96).